O direito fundamental ao desenvolvimento sustentável na era das mudanças climáticas - Wedy, Gabriel de Jesus Tedesco (2017)
This thesis proposes the idea of sustainable development as a fundamental constitutional right and duty. In this context, sustainable development is approached in the dimensions of social inclusion, governance, economic development and protection of the environment. The foundation of fundamental constitutional right and duty proposed is grounded in concepts from John Rawls's Theory of Justice as well as from the broad definition of development as freedom, coined by Amartya Sen. In the thesis, the one-size-fits-all legal arrangement model for development - which failed in Latin America and Brazil - is rejected and new proposals are adopted for legal pragmatic models with moral principles and ethical concerns. The Brazilian constitutional legal framework is analyzed, within which the fundamental right and duty to sustainable development should be funded. In addition, the extra fiscal function of taxes as behavioral reorientation is defended towards the realization of the fundamental right to sustainable development, which is incompatible with global warming. In the thesis, the principle of human dignity within the dimension of social inclusion is discussed, which makes up the proposed concept of fundamental rights to sustainable development and serves as a limiter to pragmatism. Judicial activism is regarded as inevitable in the pursuit of the realization of the fundamental right to sustainable development in the case of Brazil, where the executive branch is in charge of public policies and the laws fall short when focusing on the development issue, especially in view of the significant lack of governance that affects the scope of the three branches. In this sense, the State is proposed to be held accountable whenever the implementation of plans and projects violate the fundamental right to sustainable development. Within this thesis is a counter thesis, in the sense that there is no right to development if it is not sustainable. This denial is made with a critical analysis of doctrine and national and international jurisprudence. The thesis is a proposition of its own time, since it is inserted in the Age of Climate Change and eventually points to a failure of the National Policy of Climate Change in Brazil related to the violation of the fundamental constitutional right and duty to sustainable development, comprising the protection of a dignified life in the sense of preventing extreme climatic conditions caused by human actions.